Perception of Concreteness and familiarity of lexicon among college students. A normative study - Bargetto, Miguel A.; Riffo Ocares, Bernardo (Lenguas Modernas, 2020)
Academic literacy studies have shown that the main weakness manifested by students who join an academic community are focused on the difficulty of comprehension from their discipline. The lexicon plays an important role on this point, since the quantity and quality of the personal lexicon will influence this process. In the case of this paper, we will present the results of the normative study applied to students of the Faculty of Education of a Chilean regional university to measure the variables of concretion and familiarity. The surveys that make up this study were created from a base of 536 words, obtained from five compulsory bibliographical references of an area of sociology of education through computational analysis and refined according to criteria of extension, initial syllable and frequency. The conclusions of the paper shows that the relationships between both indices are linear, but not strong, which validates the hypothesis that the more familiar a word is, the more concrete it is perceived by the speaker. The data also establish that the words that are perceived as unfamiliar and not very specific are the least, although their distribution does not respond to a normal curve.